Polymorphisms in the DAD1 and OXA1L genes are associated with asthma and atopy in a South American population. (September 2018) - Pires, Anaque de Oliveira; Queiroz, Gerson de Almeida; de Jesus Silva, Milca; da Silva, Raimon Rios; da Silva, Hugo Bernardino Ferreira; Carneiro, Norma Vilany Queiroz; Fonseca, Héllen Freitas; de Santana, Maria Borges Rabelo; Nascimento, Regina Santos; Alcântara-Neves, Neuza Maria; Costa, Gustavo Nunes de Oliveira; Costa, Ryan dos Santos; et al.
Highlights: Genetic variants in the DAD1 and OXA1L genes are significantly associated with asthma and/or allergy markers. We have demonstrated increased DAD1 expression levels in asthmatic individuals. These variants are involved in regulatory mechanisms and may impact the occurrence of asthma and allergy in our population. Abstract: Atopic asthma, which is characterized by the chronic inflammation and morbidity of airways, is a disease of great complexity, and multiple genetic and environmental factors are involved in its etiology. In the first genome-wide association study (GWAS) conducted in Brazil for asthma, a positive association was found between atopic asthma and a variant (rs1999071), which is located between the DAD1 and OXA1L genes, although neither gene has previously been reported to be associated with asthma or allergies. The DAD1 gene is involved in the regulation of programmed cell death, and OXA1L is involved in biogenesis and mitochondrial oxidative phosphorylation. This study aimed to evaluate how polymorphisms in DAD1 and OXA1L are associated with asthma and markers of atopy in individuals from the Salvador cohort of the SCAALA (Social Change Asthma and Allergy in Latin America) program. The DNA of 1220 individuals was genotyped using the Illumina 2.5 Human Omni Bead chip. Logistic regression analyses were performed with PLINK 1.9 software to verify the association between DAD1 and OXA1L polymorphisms and asthma and atopic markers, adjusted for sex, age, helminth infections and ancestry markers, using an additive model. The DAD1 and OXA1L genes were associated with some of the evaluated phenotypes, such as asthma, skin prick test (SPT), specific IgE for aeroallergens, and Th1/Th2-type cytokine production. Using qPCR, as well as in silico gene expression analysis, we have demonstrated that some of the polymorphisms in both genes are able to affect their respective gene expression levels. In addition, DAD1 was over-expressed in asthmatic patients when compared with controls. Thus, our findings demonstrate that variants in both the DAD1 and OXA1L genes may affect atopy and asthma in a Latin American population with a high prevalence of asthma.